NSUN2‐Mediated m5C Methylation and METTL3/METTL14‐Mediated m6A Methylation Cooperatively Enhance p21 Translation - Li, Qiu; Li, Xiu; Tang, Hao; Jiang, Bin; Dou, Yali; Gorospe, Myriam; Wang, Wengong (Journal of cellular biochemistry, 2017)
ABSTRACT N6‐methyladenosine (m6A) and m5C methylation are two major types of RNA methylation, but the impact of joint modifications on the same mRNA is unknown. Here, we show that in p21 3′UTR, NSUN2 catalyzes m5C modification and METTL3/METTL14 catalyzes m6A modification. Interestingly, methylation at m6A by METTL3/METTL14 facilitates the methylation of m5C by NSUN2, and vice versa. NSUN2‐mediated m5C and METTL3/METTL14‐mediated m6A methylation synergistically enhance p21 expression at the translational level, leading to elevated expression of p21 in oxidative stress‐induced cellular senescence. Our findings on p21 mRNA methylation and expression reveal that joint m6A and m5C modification of the same RNA may influence each other, coordinately affecting protein expression patterns. J. Cell. Biochem. 118: 2587–2598, 2017. © 2017 Wiley Periodicals, Inc. In p21 3'UTR,NSUN2 catalyzes m5C modification and METTL3/METTL14 catalyzes m6A modification. Methylation at m6A by METTL3/METTL14 facilitates the methylation of m5C by NSUN2, and vice versa. NSUN2‐mediated m5C and METTL3/METTL14‐mediated m6A methylation synergistically enhance p21 expression at the translational level, leading to elevated expression of p21 in oxidative stress‐induced cellular senescence.